Education on the Importance of Adequate Iodine Intake in School Children - Rafi Syafiq Rabbani (Universitas Pendidikan Indonesia, 2022)
The purpose of this study is to educate the public about the importance of maintaining adequate daily intake of iodine. The method used is an experimental method with a quantitative approach. This research was conducted on 14 residents of Cihanjuang Village, Parongpong District, Indonesia. There are 3 main steps in carrying out this research, including (i) filling out the pre-test; (ii) provide education through animated videos; (iii) filling out the post-test questionnaire. From the results of the study showed an increase from the results of the pretest score to the posttest with a value of 45 to 82.5. while the N-Gain results obtained were 71%, meaning that education for the people of Cihanjuan Village, Parongpong District about the importance of adequate iodine intake for school children is quite effective. The t-test carried out also concluded that the results of t count t table, with numbers -9.449 1.77093 which means that the posttest score of respondents increased not significantly. With the implementation of this research, it is hoped that more people will become aware of the importance of maintaining daily iodine intake, especially for school children. So that IDD (Iodine Deficiency Disorders) can be avoided.